Detection rate of ureteric stones with ultrasonography and relationship with grade of hydronephrosis - Kafle, Pankaj (Asian Journal of Medical Sciences, 2018)
Background: Ultrasound scanning can serve as reliable, basic first line mode of imaging techniques in detecting ureteric stone in patients with hydronephrosis and grade them accordingly with or without need of other imaging techniques. Aims and Objective: To evaluate the relationship between the degree of hydronephrosis and the detection rates of ureteral stones with ultrasonography in computed tomography or intravenous urography proven cases of ureteric calculi. Materials and Methods: This was a prospective observational study involving 75 patients with computed tomography or intravenous urography diagnosis of ureteric calculi. Both kidneys were observed by ultrasonography to evaluate the intrarenal collecting systems for hydronephrosis.Thereafter, the ureters were evaluated in four different locations to find any stone. The hydronephrosis was graded as mild, moderate and severe according to the dilatation of the pelvic calyceal system with or without stones. Detection rate of ureteric calculi was then estimated. Results: A total of 75 cases were evaluated. Stones were clearly observed in 51 of 59 (86.4%) patients with calyceal dilatation, whereas stones were detected in 9 of 16 (56.3%) patients without dilatation (p<0.05). Out of 75 patients, 38 (50.7%) had stones in the ureterovesical junction, 12 (16%) had stones in the proximal ureter, 5(6.7%) in the iliac cross, 5(6.7%) in distal ureter and 15(20%) were undetected. Out of 15 undetected stones, 8(13.6%) had calyceal dilatation and 7(43.8%) without calyceal dilatation. Conclusion: The ultrasonography detection rate of ureteral stones was high in patients with calyceal dilatation. The whole ureter should be scanned in patients with calyceal dilatation for detection of ureteral stones. Even when patients have no calyceal dilatation, it is still considered to be useful to scan the ureterovesical junction. Asian Journal of Medical Sciences Vol.9(3) 2018 17-20